Elevated macrophage-inducible C-type lectin expression in the synovial tissue of patients with rheumatoid arthritis - Ken Takata; Shotaro Takano; Masayuki Miyagi; Manabu Mukai; Dai Iwase; Jun Aikawa; Yoshihisa Ohashi; Gen Inoue; Masashi Takaso; Kentaro Uchida (Central European Journal of Immunology, 2021)
Rheumatoid arthritis (RA), a systemic autoimmune disease, is known to cause chronic inflammation in synovial joints. A number of inflammatory conditions are associated with stimulation of Clec4e, a macrophage-inducible C-type lectin (MINCLE) and transmembrane pattern recognition receptor that functions in innate immunity. We previously reported MINCLE expression in synovial macrophages isolated from the synovium of osteoarthritis (OA) patients. However, MINCLE expression has not been examined in RA synovial tissue. To examine MINCLE expression in RA patients, synovial tissue specimens were obtained from patients with RA and OA during joint replacement surgery (n = 20 each). Total RNA was extracted from synovial tissue and used to compare MINCLE expression in OA and RA (n = 15 each). We also extracted fresh CD14+ (macrophage-rich) and CD14– cell fractions from synovial tissue and compared MINCLE expression between OA and RA patients (n = 5 each). MINCLE levels in synovial tissue were significantly elevated in RA patients compared to OA patients. MINCLE expression was significantly elevated in the CD14+ fraction compared to the CD14– fraction in both OA and RA patients. Further, while there were no differences in the CD14+ fraction between RA and OA, MINCLE expression in the CD14– fraction was elevated in RA compared to OA. Our findings indicate that MINCLE expression is elevated in the synovium of RA patients and that MINCLE expression in non-macrophage cell fractions may be a key feature of RA.